2019
DOI: 10.1038/s41419-019-1512-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of USP2 eliminates cancer stem cells and enhances TNBC responsiveness to chemotherapy

Abstract: Triple-negative breast cancer (TNBC) is the most aggressive subtype of breast cancer that harbors enriched cancer stem cell (CSC) populations in tumors. Conventional chemotherapy is a standard treatment for TNBC, but it spares the CSC populations, which cause tumor recurrence and progression. Therefore, identification of the core molecular pathway that controls CSC activity and expansion is essential for developing effective therapeutics for TNBC. In this study, we identify that USP2 deubiquitinating enzyme is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 55 publications
0
56
0
Order By: Relevance
“…USP2 was identified to be up-regulated in patients with metastasis, and then upon further clinicopathological assessment, USP2 enrichment was detected in TNBC relative to that in non-TNBC [92]. He et al found that silencing USP2 in TNBC reduced mammosphere formation and chemoresistance [93]. Their study showed that USP2 stabilized Twist by cleaving proteolytic ubiquitination, and Twist increased the transcription of Bmi1, which is a polycomb complex protein that controls the self-renewal and pluripotency of stem cells [93].…”
Section: Approaches For Targeting the Self-renewal Process In Tnbcmentioning
confidence: 99%
See 2 more Smart Citations
“…USP2 was identified to be up-regulated in patients with metastasis, and then upon further clinicopathological assessment, USP2 enrichment was detected in TNBC relative to that in non-TNBC [92]. He et al found that silencing USP2 in TNBC reduced mammosphere formation and chemoresistance [93]. Their study showed that USP2 stabilized Twist by cleaving proteolytic ubiquitination, and Twist increased the transcription of Bmi1, which is a polycomb complex protein that controls the self-renewal and pluripotency of stem cells [93].…”
Section: Approaches For Targeting the Self-renewal Process In Tnbcmentioning
confidence: 99%
“…He et al found that silencing USP2 in TNBC reduced mammosphere formation and chemoresistance [93]. Their study showed that USP2 stabilized Twist by cleaving proteolytic ubiquitination, and Twist increased the transcription of Bmi1, which is a polycomb complex protein that controls the self-renewal and pluripotency of stem cells [93]. Davis et al developed the USP2-specific inhibitor ML364, which directly binds and inhibits the enzymatic activity of USP2 [94].…”
Section: Approaches For Targeting the Self-renewal Process In Tnbcmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, hedgehog signaling drives to stemness, invasion, and EMT of BCSCs (103). In addition, USP2 activates Bmi1 and EMT by stabilizing Twist through removing ubiquitylation mediated by beta-transducin repeats-containing proteins (β-TrCP), a cellular E3 ubiquitin ligase (104).…”
Section: Metastasis In Bcscsmentioning
confidence: 99%
“…Therefore, eradication of CSCs is a potential therapeutic avenue to increase the survival rate of EOC patients. Recently, studies have shown that targeting key molecular players and genetic aberrations in CSCs using small molecule inhibitors, including rapamacyin and triciribine can eradicate CSCs in brain tumors and improve overall survival in glioblastoma and neuroblastoma patients [ 4 , 8 , 9 , 10 , 11 , 12 ]. Identifying the molecular signature of ovarian CSCs will provide a novel therapeutic strategy to selectively target this subpopulation of cells and improve overall survival.…”
Section: Introductionmentioning
confidence: 99%